Escalating wind power shortages during heatwaves - Jiewen You; Fangxu Yin; Lu Gao (Communications Earth & Environment)
Abstract Heatwaves challenge electricity systems relying on wind energy for renewable power. However, the global availability of wind power during heatwaves remains unknown. Here, we provide a global assessment of wind power dynamics during heatwaves using weather reanalysis data from 1980 to 2023. Our results show the global land area experiencing wind power shortages during heatwaves has risen by 6.3% per decade, reaching 60% by 2023. Australia, Northern Asia, and Europe are particularly vulnerable, with wind power decreasing by 30–50%. Conversely, regions such as the Amazon, the Great Plains in North America, and Central Africa experience slight increases in wind power during heatwaves. 75.5% of land areas show a negative response between maximum temperatures and wind speeds. Our findings highlight the growing risk of concurrent heatwaves and wind power shortages, underscoring the need for targeted regional strategies to ensure the reliability of wind energy systems under a warming climate.